International Law of Victims - Fernández de Casadevante Romani, Carlos. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
After having ignored victims, only recently both domestic and international law have begun to pay attention to them. As a consequence, different international norms related to victims have progressively been introduced. These are norms generally characterized by a certain concept from the perspective of victims, as well as by the enumeration of a list of rights to which they are entitle to; rights upon which the international statute of victims is built. In reverse, these catalogues of rights are the states’ obligations. Most of these rights are already existent in the international law of human rights. Consequently, they are not new but consolidated rights. Others are strictly linked to victims,  concerning the following categories: victims of crime, victims of abuse of power, victims of gross violations of international human rights law, victims of serious violations of international humanitarian law, victims of enforced disappearance, victims of violations of international criminal law and victims of terrorism.